Agricultural Transformation around Koshi Hill Region: A Rural Development Perspective - Timalsina, Tirtha Raj (NUTA Journal, 2019)
Agriculture is considered to be the basic segment and the backbone of developing economy. In the same way it is a prime and dominant sector of Nepalese rural livelihood. By considering this fact, the true value of rural development lies on the rapid transformation of existing agricultural sector. The aim of this study is to analyze the role of agricultural transformation for rural development of Koshi Hill Region (KHR) of eastern Nepal. Both the primary as well as secondary data and information have been used to obtain the required findings. The study reveals the fact that agriculture is inevitable for rural people and its transformation is essential for the development of rural areas and the nation as a whole. Including primarily to the road network, the development of infrastructure can play the detrimental role to change the backward and rural scenario of this country.